Li Shaobai: From Pioneer Film Researcher to “Dead Tiger” to Grand Old Mentor of Film Studies - Lent, John A. (Asian Cinema, 2006)
Li Shaobai has had a distinguished -- at times life changing-- career in China’s film studies. He, Cheng Jihua, and Xing Zuwen produced Zhong Guo Dian Ying Fa Zhan Shi in 1963, the first major history of Chinese cinema and the subject of much criticism leading to all three authors being severely punished during the “Cultural Revolution.” Li also was responsible for establishing early film research groups, such as the China Film Art Research Center in 1974 and later, the Chinese Film and Television Research Institute under the Academy of Chinese Art. The latter was the first institution to grant both the masters (in 1982) and Ph. D. (in 1995) degrees in film studies in China, and, as a result, Li Shaobai became the mentor of the first batch of Chinese film researchers. His first MA students were Chen Xihe, Bao Yuheng, Zhong Dafeng, Zhang Aihua, and Wang Hanchuan; the first two doctoral students at CFTRI were Ding Yaping and Li Daoxing, followed by Shi Chuan. He said today, four Ph. D. programs in film studies exist in Beijing: CFTRI, Beijing Normal University, Beijing Film Academy, and Communication University of China.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4xNy4xLjQzXzE